Epidemiological trends and healthcare disparities in onychomycosis: An analysis of the All of Us research program. - Aditya K Gupta; Vasiliki Economopoulos; Tong Wang; Vincent Piguet (PLoS ONE)
Onychomycosis is a common, difficult to treat nail disorder. Our objective was to explore disparities in current clinical management practices for onychomycosis in patients from underrepresented groups and with specific comorbidities. We conducted a cross-sectional study using the All of Us (AoU) research program. The AoU program gathers survey, and electronic health records from participants in the United States with the aim of increasing the representation of minorities groups in health research under the framework of precision medicine. We identified 18,763 onychomycosis patients (2017-2022) and compared the rates of diagnostic testing, prescription medications and surgical procedures. Younger patients were more likely to receive oral medications, while older patients were more likely to undergo surgical nail procedures. Patients with lower income and education, Black and Hispanic patients were less likely to receive testing to confirm diagnosis, and less likely to receive prescription medications (topical and/or oral) except in the case of fluconazole. Lower income and education were associated with a higher likelihood of debridement and trimming procedures, while Black and Hispanic patients were less likely to undergo these procedures. Patients with disabilities also received different treatments when compared to able-bodied individuals, being less likely to receive ciclopirox, efinaconazole and terbinafine, but more likely to undergo debridement and trimming procedures. There are clear differences in the management of onychomycosis in the different demographic and comorbid populations that we studied. Efforts to reduce these inequalities, such as expanded health coverage, reducing communication barriers and increasing patient and physician education are needed.